Proposed Business Strategy of Joint Operation with the Implementation of New Terms & Conditions in Pertamina EP Regional 1 - Wandebori, Harimukti; Pratama, Ridho (Riviera Publishing, 2026)
Indonesia’s upstream oil and gas sector serves as a cornerstone of national energy security, with Pertamina EP (PEP) acting as one of the primary contributors through its extensive cooperation contract areas. In 2023, PEP achieved significant milestones, including 159.12 MMBOE in 2C contingent resource discoveries and a 217% increase in proven reserves compared to the previous year. To accelerate production and strengthen collaboration, PEP engages in Joint Operating Agreements (JOAs) with joint venture partners—structured partnerships aligned with the Production Sharing Contract (PSC) framework under the supervision of SKK Migas. While the JOA model has facilitated shared investment, expertise, and operational responsibilities, its current terms and conditions are perceived as outdated and overly stringent, thereby limiting partner eligibility, discouraging investment, and concentrating production risk on joint venture partners. This study addresses these challenges by proposing a revised business strategy for joint operations under new JOA terms and conditions designed to create a more balanced, attractive, and performance-driven framework. The research employs stakeholder analysis, internal and external business environment assessment, and strategic formulation models to identify opportunities for improvement. Data collection involves Focus Group Discussions (FGDs) with Subject Matter Experts (SMEs) and secondary sources, including operational records, internal reports, and relevant literature. Findings indicate that implementing the proposed terms and conditions—focused on fair cost recovery, equitable risk sharing, and an adjusted production split—can enhance operational efficiency, increase investor confidence, and align stakeholder interests. This study contributes a strategic roadmap for PEP to strengthen partnerships, improve production outcomes, and sustain competitiveness in Indonesia’s dynamic oil and gas industry.